Pengaruh Fleksibilitas Waktu Belajar Daring terhadap Hasil Belajar Mahasiswa - Fawwaz Akif Prayoga; Laila Fitria; Muhammad Munawwirul Hayat; Rissa Yulinda; Siti Suaibah Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the effect of time flexibility in the implementation of online-based learning on student academic performance in the Management Study Program, State Islamic University of North Sumatra (UINSU). This study adopts a quantitative approach as the main method. Data collection instruments in the form of questionnaires were distributed to active students as respondents. The data obtained were then analyzed using simple linear regression techniques to illustrate the relationship between the level of flexibility of study time and student academic achievement. The results of the analysis show that the flexibility of study time has no significant effect on student learning outcomes, with a significance value of 0.315 and a coefficient of determination (R²) of 0.027. This finding indicates that flexibility of study time is not enough to improve learning outcomes without being supported by time management skills, discipline, and learning independence. Therefore, effective online learning strategies need to be accompanied by soft skills training so that learning outcomes can be optimized. Future research is expected to integrate mediating variables such as self-regulated learning, learning motivation, and quality of learning environment to gain a deeper understanding of the determinants in the context of online learning.